NAD + Replenishment Improves Lifespan and Healthspan in Ataxia Telangiectasia Models via Mitophagy and DNA Repair - Fang, Evandro Fei; Kassahun, Henok; Croteau, Deborah L; Scheibye-Knudsen, Morten; Marosi, Krisztina; Lu, Huiming; Shamanna, Raghavendra A; Kalyanasundaram, Sumana; Bollineni, Ravi Chand; Wilson, Mark A; Iser, Wendy B; Wollman, Bradley N; et al. (Cell metabolism, 2016)
Ataxia telangiectasia (A-T) is a rare autosomal recessive disease characterized by progressive neurodegeneration and cerebellar ataxia. A-T is causally linked to defects in ATM, a master regulator of the response to and repair of DNA double-strand breaks. The molecular basis of cerebellar atrophy and neurodegeneration in A-T patients is unclear. Here we report and examine the significance of increased PARylation, low NAD , and mitochondrial dysfunction in ATM-deficient neurons, mice, and worms. Treatments that replenish intracellular NAD reduce the severity of A-T neuropathology, normalize neuromuscular function, delay memory loss, and extend lifespan in both animal models. Mechanistically, treatments that increase intracellular NAD also stimulate neuronal DNA repair and improve mitochondrial quality via mitophagy. This work links two major theories on aging, DNA damage accumulation, and mitochondrial dysfunction through nuclear DNA damage-induced nuclear-mitochondrial signaling, and demonstrates that they are important pathophysiological determinants in premature aging of A-T, pointing to therapeutic interventions.